2021
DOI: 10.1523/jneurosci.1944-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Neurons of the Bed Nucleus of Stria Terminalis Enhance Associative Fear Memory Consolidation in Mice

Abstract: Excessive fear learning and extinction-resistant fear memories are core symptoms of anxiety and trauma-related disorders. Despite significant evidence from clinical studies reporting hyperactivity of the bed nucleus of stria terminalis (BNST) under these conditions, the role of BNST in fear learning and expression is still not clarified. Here, we tested how BNST modulates fear learning in mice using a chemogenetic approach. Activation of GABAergic neurons of BNST during fear acquisition, more specifically the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 74 publications
3
12
0
Order By: Relevance
“…All animals with virus extension outside of the BNST were excluded from the analysis (N = 2–9/group: N = 5–6 of control and N = 7–9 of hM4Di subjects in case of sst-ires-cre mice; N = 2–3 of control and N = 4–9 of hM4Di subjects in case of crh-ires-cre mice). Generally, mCherry-positive cell bodies were observed along the whole rostrocaudal axis of the BNST similar to our previous studies ( Bruzsik et al, 2021 ).…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…All animals with virus extension outside of the BNST were excluded from the analysis (N = 2–9/group: N = 5–6 of control and N = 7–9 of hM4Di subjects in case of sst-ires-cre mice; N = 2–3 of control and N = 4–9 of hM4Di subjects in case of crh-ires-cre mice). Generally, mCherry-positive cell bodies were observed along the whole rostrocaudal axis of the BNST similar to our previous studies ( Bruzsik et al, 2021 ).…”
Section: Methodssupporting
confidence: 90%
“…Recently, we also showed that hyperactivity of BNST SST neurons enhance fear consolidation, and subsequent freezing during fear recalls in a safe context without affecting the acute fear response when strong aversive (i.e. footshock) stimuli are present in a predictable way ( Bruzsik et al, 2021 ). Together these results support the notion that BNST SST neurons promote passive fear responses to low intensity/uncertain threats, which can be a complementary function to central amygdala (CeA) circuits, where CeA SST neurons are engaged under imminent threat conditions and drive passive fear response to direct/strong threats, including a high dose of 2MT ( Andraka et al, 2021 ; Isosaka et al, 2015 ; K. Yu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the ICV injection of CRH induced c-Fos expression in BNST (Arnold et al 1992) and CRH microinjection into BNST increased heart rate (Nijsen et al 2001). Based upon pharmacogenetic examinations CRH neurones of the BNST do not seem to participate in modulation of fear (Bruzsik et al 2021).…”
Section: Bed Nucleus Of Stria Terminalis (Bnst)mentioning
confidence: 93%
“…A number of studies have shown that activity of L-type of VGCCs can be regulated by eCBs, mainly by the CB1R [ 100 , 101 ]. Electrophysiological and pharmacological data showed that activation of dendritic L-type Ca 2+ channels and the subsequent release of 2-AG acting on the presynaptic CB1 receptors triggered retrograde short-term depression (STD) in bed nucleus of the stria terminalis (BNST) neurons and in spiny neurons in corticostriatal slices [ 102 ]. In both rodents and humans, the BNST has prominent white matter connectivity with the amygdala via the stria terminalis, as well as with the inferior hippocampus, hypothalamus, thalamus, and infralimbic/ventromedial prefrontal cortex.…”
Section: Regulation Of Voltage-gated Ca 2+ Channels and Other Ca 2+ -Permeable Channels By Ecbsmentioning
confidence: 99%